2015
DOI: 10.3390/rs71215860
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the Photochemical Reflectance Index to Track Light Use Efficiency for a Sub-Tropical Planted Coniferous Forest

Abstract: Light use efficiency (LUE) models are widely used to estimate gross primary productivity (GPP), a dominant component of the terrestrial carbon cycle. Their outputs are very sensitive to LUE. Proper determination of this parameter is a prerequisite for LUE models to simulate GPP at regional and global scales. This study was devoted to investigating the ability of the photochemical reflectance index (PRI) to track LUE variations for a sub-tropical planted coniferous forest in southern China using tower-based PRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
29
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 95 publications
(159 reference statements)
7
29
1
1
Order By: Relevance
“…It is likely that the difference in daily PRI among seasons was partially caused by the seasonal changes in pigment pool size as frequently stated by previous studies (Gamon et al, 2016), but this long-term pigment regulatory mechanism may play a minor role in determining the seasonality of PRI in subtropical mangrove ecosystems. The weak seasonal PRI difference in mangrove forests is not in agreement with the hump-shaped seasonal patterns from previous studies in boreal evergreens (Soudani et al, 2014;Wong & Gamon, 2015), but it is comparable to other subtropical forest types (Zhang et al, 2015;Zhang et al, 2017). These contrasting findings are reasonable given that there was much smaller seasonal temperature difference in subtropical evergreens compared to boreal evergreens.…”
Section: 1029/2019jg005022contrasting
confidence: 84%
“…It is likely that the difference in daily PRI among seasons was partially caused by the seasonal changes in pigment pool size as frequently stated by previous studies (Gamon et al, 2016), but this long-term pigment regulatory mechanism may play a minor role in determining the seasonality of PRI in subtropical mangrove ecosystems. The weak seasonal PRI difference in mangrove forests is not in agreement with the hump-shaped seasonal patterns from previous studies in boreal evergreens (Soudani et al, 2014;Wong & Gamon, 2015), but it is comparable to other subtropical forest types (Zhang et al, 2015;Zhang et al, 2017). These contrasting findings are reasonable given that there was much smaller seasonal temperature difference in subtropical evergreens compared to boreal evergreens.…”
Section: 1029/2019jg005022contrasting
confidence: 84%
“…Moreover, there are reports of difficulties with tracking LUE changes in drought-stressed vegetation that may originate from enhancement of respiration processes [74][75][76]. Probably due to interference with respiration we were also unable to distinguish between the effects of low temperature (HI-LT) versus the combined drought and high temperature stress (HI-HT3) using PRI in our dataset ( Figure 7A,B).…”
Section: Evaluation Of Water Limitation From Primentioning
confidence: 68%
“…Light use efficiency (LUE) is determined by environmental factors such as nutrients, moisture, and atmospheric temperature, resulting in differences in time and space in the photochemical reaction process. The photochemical reflectance index (PRI), based on remote sensing technology, provides the possibility to establish a link between changes in LUE and changes in the spectral characteristics of vegetation [9][10][11]. Some previous studies have shown that LUE is not a constant value in different ecosystems [12].…”
mentioning
confidence: 99%
“…Using different fitting methods, the impact of VPD on the relationship between PRI and LUE was 34% and 38% [29]. Zhang et al research in subtropical coniferous forests showed that the correlation between PRI and LUE at half-hour and daily scales was 20% and 29%, respectively, and the correlation was small in suitable growth environments [10].The distribution of leaves in the vegetation canopy will affect the interception of solar radiation and the efficiency of light utilization. Lidar scans can more accurately retrieve vegetation canopy structural parameters [30].…”
mentioning
confidence: 99%